Computational mechanics analysis in elevated shell platform structures / Azizah Abdul Nassir, Yee Hooi Min and Syahrul Fithry Senin - Abdul Nassir, Azizah; Yee, Hooi Min; Senin, Syahrul Fithry (Universiti Teknologi MARA, 2021)
Shell structures are usually used in roof applications and aerospace structures. The advantage of these structures is not fully utilized in transmitting applied force. A thin-shell structure can be used for building construction and aerospace structures due to its lightweight nature. The township high load in this study refers to the high-speed airflow in the case of aerospace. This study was conducted to justify the feasibility of applying a thin-shell structure as an elevated shell platform for township foundations, where several different geometries were analyzed using finite element analysis (FEA) and artificial neural network (ANN). In the findings, all maximum stresses from different geometries are lower than the design value, thus verifying the feasibility of constructing a shell platform for heavy loading applications. The regression plots from the ANN output show that all geometries approached the value of 1, which means that the predicted ANN output and actual datasets of FEA are almost similar. From the ANN predicted output, the mean square error (MSE) was calculated. All the MSE values obtained from each geometry approached zero, indicating the analysis is precise and has a minimal error. Thus, this study has justified the feasibility of proposing elevated shells for township applications, which can be used as a reference in the design phase for future implementation.